Ethylene and RIPENING INHIBITOR Modulate Expression of SlHSP17.7A, B Class I Small Heat Shock Protein Genes During Tomato Fruit Ripening - Upadhyay, Rakesh K.; Tucker, Mark L.; Mattoo, Autar K. (Frontiers in Plant Science, 2020)
Heat shock proteins (HSPs) are ubiquitous and highly conserved in nature. Heat stress upregulates their gene expression and now it is known that they are also developmentally regulated. We have studied regulation of small HSP genes during ripening of tomato fruit. In this study, we identify two small HSP genes, SlHSP17.7A and SlHSP17.7B, localized on tomato Chr.6 and Chr.9, respectively. Each gene encodes proteins constituting 154 amino acids and has characteristic domains as in other sHSP genes. We found that SlHSP17.7A and SlHSP17.7B gene expression is low in the vegetative tissues as compared to that in the fruit. These sHSP genes are characteristically expressed in a fruit-ripening fashion, being upregulated during the ripening transition of mature green to breaker stage. Their expression patterns mirror that of the rate-limiting ethylene biosynthesis gene ACC (1-aminocyclopropane-1-carboxylic acid) synthase, SlACS2, and its regulator SlMADS-RIN. Exogenous application of ethylene to either mature green tomato fruit or tomato leaves suppressed the expression of both the SlHSP17.7A, B genes. Notably and characteristically, a transgenic tomato line silenced for SlACS2 gene and whose fruits produce ~50% less ethylene in vivo, had higher expression of both the sHSP genes at the fruit ripening transition stages [breaker (BR) and BR+3) than the control fruit. Moreover, differential gene expression of SlHSP17.7A versus SlHSP17.7B gene was apparent in the tomato ripening mutants - rin/rin, nor/nor and Nr/Nr, with the expression of SlHSP17.7A being significantly reduced but that of SlHSP17.7B significantly upregulated as compared to the wildtype (WT). These data indicate that ethylene negatively regulates transcriptional abundance of both these sHSPs. Transient overexpression of the ripening regulator SlMADS-RIN in WT and ACS2-AS mature green tomato fruits suppressed the expression of SlHSP17.7A but not that of SlHSP17.7B. Thus, ethylene directly or in tune with SlMADS-RIN regulates the transcript abundance of both these sHSP genes.